2018
DOI: 10.1038/s41598-018-35061-8
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of Dryopteris fragrans (L.) Schott and the repeat structures against the thermal environment

Abstract: Dryopteris fragrans (L.) Schott is a fern growing on the surface of hot rocks and lava. It is exposed to sunlight directly and bears local hot environment. We sequenced the complete nucleotide sequence of its chloroplast (cp) genome. The cp genome was 151,978 bp in length, consisting of a large single-copy region (85,332 bp), a small single-copy region (31,947 bp) and a pair of inverted repeats (17,314 bp). The cp genome contained 112 genes and 345 RNA editing sites in protein-coding genes. Simple sequence rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
6
14
0
Order By: Relevance
“…Most editing events in these four chloroplast genomes were C-to-U events in this study, which is consistent with D. fragrans [26]. It has been reported that the excess of C-to-U RNA editing developed in early stages of vascular plant evolution [46].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Most editing events in these four chloroplast genomes were C-to-U events in this study, which is consistent with D. fragrans [26]. It has been reported that the excess of C-to-U RNA editing developed in early stages of vascular plant evolution [46].…”
Section: Discussionsupporting
confidence: 87%
“…goeringiana and P. tripteron for the first time, ranging from 148,539 bp to 151,341 bp in length. The whole chloroplast genomes size of more than 20 ferns were compared in the study of Gao et al [26] and RuizRuano et al [1], which revealed that the length of ferns ranging between 131,760 bp (Equisetum hyemale) and 181,684 bp (C. devexiscapulae) based on the current researches, and the four ferns detected in our study is within this range. The genomes of these four ferns chloroplast exhibit a typical quadripartite structure, including LSC, SSC and two IRs, as reported in other spore plants [27,28].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations